(untitled) (International Journal of Food and Nutritional Sciences, 2018)
This article deals with relevant gender problems which are common in women entrepreneurs in Manipur, from the lens of globalization. Competition to reduce the throat is an integral part of the globalization process, which requires only the best for survival. But in our patriarchal society, women entrepreneurs have to face various gender-related discriminations. Many socio-cultural obstacles arise from the proposal of a business to the distribution of the scope of financial matters. Restrictions in mobility in the area and time hamper their chances of active competition with global giants. This type of gender disparities is also commonly visible in many support institutions. Moreover, globalization itself constitutes a gender bias in the Manipur branch: women entrepreneurs are forced to compete in the low-cost informal sector, while male entrepreneurs prefer the high-risk, modernised sector. Women have lost their traditional activities due to the large influx of goods from neighboring countries that came with trade liberalization as part of the national economic policy after 1991. Overall, women entrepreneurs have been the biggest losers in this process, with no benefits and facing major problems. Thus, this article will bring viable measures that allow women entrepreneurs to join and take advantage of globalization.